Relationship between body mass index with dental caries and the effect of socio-economic status in rural and urban in Indonesia in the year of 2018 - Fuad Husain Akbar (Makassar Dental Journal PDGI Makassar, 2020)
Introduction: Oral diseases with high prevalence in Indonesia are caries. Dental caries takes months or years to develop in most people. It is influenced by theconsumption of food sugars, salivary flow, fluoride exposure, and preventive procedures such as tooth brushing and routine examination. Aim: Relationship between body mass index with dental caries and the effect of socioeconomic status in rural and urban in Indonesia in the year of 2018 Method: Survey ofpilot pathfinder conducted in urban and rural areas of Gowa District, South Sulawesi, Indonesia in 2018 with a total number of subjects 416 people aged 11-14 years old. Result: Based on age, subjects in urban areas were highest at age 12 years (44.8%), whereas in rural area the most subjects were at the age of 11 years (37.9%). Based on sex, subjects in urban areas were 104 men (49.5%) and women 106 people (50.5%), while in rural areas were men 105 people (51.0%) and women 101 (49.0%). Discussion: There are conflicting findings from research on the population of adolescents in Gowa. In urban area of Somba Opu subdistrict, there is a relationship between BMI category and revenue to caries, whereas in rural area of Pattalassang subdistrict, there is a cor-relation between BMI category and occupation on caries. Conclusion: Overall BMI associated with dental caries. Although statistically significant the caries prevalence and experience were lower in overweight children in both the urban and rural areas of Gowa District.